Pregnancy Outcomes in Women with Arrhythmias following Surgical Repair of Cardiac Defects - Chornock, Rebecca; Lewis, Dana; Gabaud, Stephany; Fries, Melissa; Greenberg, Victoria; Kawakita, Tetsuya (American Journal of Perinatology, 2022)
Objective The goal of this study was to investigate whether preexisting cardiac arrhythmias are associated with adverse obstetrical outcomes in women with a history of open cardiac surgery.Study Design This was a retrospective cohort study of women with a history of open cardiac surgery who delivered at MedStar Washington Hospital Center (Washington, DC) from January 2007 through December 2018. Women with the isolated percutaneous cardiac surgical repair were excluded. Maternal and neonatal outcomes were compared between patients with preexisting cardiac arrhythmias and patients without preexisting cardiac arrhythmias. Maternal outcomes studied were intensive care unit admission, postpartum blood loss greater than 1,000 mL, congestive heart failure development, preeclampsia with severe features, postpartum readmission, postpartum cardiac events, and postpartum length of stay >5 days. Neonatal outcomes investigated were low birth weight <2,500 g, Apgar's scores <7 at 5 minutes, and neonatal intensive care unit admission. Multivariate logistic regression model was used to calculate the adjusted odds ratio (aOR) and 95% confidence intervals.Results The outcomes for 69 deliveries from 56 women with a history of open cardiac surgery were examined. Thirty-three women (48%) had arrhythmias after cardiac surgery with fourteen (20%) requiring implantable cardioverted defibrillators. Two women (6%) with preexisting arrhythmias after cardiac surgery developed postpartum volume overload requiring readmission (p = 0.06). After controlling for age, gestational age at delivery, and BMI, preeclampsia with severe features (p = 0.02) and low birth weight neonates (p = 0.02, aOR = 2.26 [0.56–9.03]) remained statistically more like to occur in patients with preexisting cardiac arrhythmias than in patients without preexisting arrhythmias.Conclusion Women with a history of open cardiac surgery and preexisting cardiac arrhythmias prior to pregnancy are more likely to develop preeclampsia with severe features and have low birth weight neonates compared with women with a history of open cardiac surgery without preexisting cardiac arrhythmias.Key Points
Keywords: arrhythmia; pregnancy; congenital cardiac disease; cardiac surgery